2017
DOI: 10.1111/acem.13209
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Study Medical Decision Making in the Clinical Setting: The “Own‐point‐of‐view” Perspective

Abstract: Background: Making diagnostic and therapeutic decisions is a critical activity among physicians. It relies on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
9
0
6
Order By: Relevance
“…Pioneered in the 1990s (Omodei & McLennan, 1994;Pelaccia et al, 2017), the RVPwSAR offers promising avenues of inquiry into real-time decision-making, attention, and reasoning (Omodei & McLennan, 1994;Pelaccia et al, 2017). Research conducted on work domain analysis showed that the subjective aided recall method "reduces bias in self-report protocols" (Miller, 2004(Miller, , p. 1643 and, in the domain of sport, Mackenzie and Kerr (2012) concluded that despite its own potential biases, this method "[.…”
Section: Retrospective Verbal Protocol With Subjective Aided Recall (...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneered in the 1990s (Omodei & McLennan, 1994;Pelaccia et al, 2017), the RVPwSAR offers promising avenues of inquiry into real-time decision-making, attention, and reasoning (Omodei & McLennan, 1994;Pelaccia et al, 2017). Research conducted on work domain analysis showed that the subjective aided recall method "reduces bias in self-report protocols" (Miller, 2004(Miller, , p. 1643 and, in the domain of sport, Mackenzie and Kerr (2012) concluded that despite its own potential biases, this method "[.…”
Section: Retrospective Verbal Protocol With Subjective Aided Recall (...mentioning
confidence: 99%
“…composing, or improvising). This method has shown great potential for the study of real-time decision-making in sport and refereeing (Mackenzie & Kerr, 2012;Omodei & McLennan, 1994;Rix & Biache, 2004;Rix-Lièvre et al, 2013;Sparkes & Smith, 2012;Williams & Ericsson, 2005), clinical and emergency situations (Miller, 2004;Omodei et al, 2005;Pelaccia et al, 2017;Unsworth, 2005), and consumer behavior (Büttner & Silberer, 2008). This article reviews research methods studying real-time decision-making and discusses the implications of a study using RVPwSAR to observe decision-making strategies during musical improvisation.…”
Section: Introductionmentioning
confidence: 99%
“…The own-point-of-view video generated by this tool has been shown to stimulate recall, leading to more explicit descriptions of decisionmaking resulting from improved psychological immersion of participants. 23 Figure 2 shows a screen shot of video output.…”
Section: Protocol For Simulation Sessionsmentioning
confidence: 99%
“…After this traditional feedback session, residents completed an additional 30-minute individual debriefing session (the focus of this study). During this session, another emergency physician (A.S.) guided residents through a cognitive-task analysis using a subjective re-situ interview protocol, 23 in which residents viewed their first-person video performance, starting when they began to read the first clinical vignette. A.S. had previous experience with this type of interviewing technique.…”
Section: Feedback and Cognitive Task Analysismentioning
confidence: 99%
“…[5][6][7][8] These decisions range from attributing a diagnosis (or at least reaching a sufficient understanding of a clinical problem to direct management) to ordering investigations and determining optimal management (defined by Cook et al 9 as "choices about treatment, follow-up visits, further testing, and allocation of limited resources," which would include resuscitation, admission, and discharge in the emergency setting). 7,10 In the literature, many terms are used to describe clinical reasoning, including "critical thinking," "problem solving," "diagnostic reasoning," and even "decisionmaking." 11,12 Many authors use them interchangeably, whereas others do not.…”
Section: Introductionmentioning
confidence: 99%